Examining Public Administration Through the Islamic Lens: A Glimpse of the Malaysian Experience - Rahman, Nurulhasanah Abdul; Abdul Hamid, Ahmad Fauzi (Universitas Islam Negeri Mataram, 2024)
The Malaysian government has undertaken significant efforts to improve public services. However, applying Islamic approaches in the public sector is increasingly wavering today. Internal conflicts and power transitions have also hampered the efficiency of public administration. While Islam is recognized in the federal constitution, governance principles are not confined to Islamic regulations alone. Past policies, such as the Inculcation of Islamic Values and Islam Hadhari, have promoted Islamic values in public service and have been embraced by citizens of all ethnicities. This article provides a transparent review of the actual situation in Malaysia, highlighting that while these concepts are present, their implementation has often fallen short, and public appreciation of these principles needs to be more superficial. This study employed secondary data from past literature on public administration and Islam, relying on an extensive review of existing scholarly works and historical records. Findings reveal that in Malaysia, each leader seems to have their interpretation of Islamic concepts for their premiership, leading to inconsistent application of these principles. However, the Khalifah concept is recommended for Malaysian public administration. By embracing Khalifah, Malaysian leaders can revitalize public administration by prioritizing courtesy and values rooted in the Islamic faith, effectively addressing issues such as abuse of power, corruption, and breaches of trust among civil servants.